(untitled) (Heritage, 2025)
This scientific paper analyzes aspects of the actions of the Kosovo Liberation Army (KLA) in the context of armed conflicts in the Balkans, with the aim of determining the extent to which the activities of this organization can be qualified as terrorism. The focus is on specific actions, methods, and goals of the KLA in accordance with scientific definitions of terrorism. Theoretical approaches to terrorism and the historical context of the KLA’s emergence are considered. Through the analysis of the KLA’s actions, goals, and methods, as well as the consequences of its activities, the paper seeks to answer the question of the extent to which the KLA’s actions constituted terrorism.